NSAIDs and Tonsillectomy: A Systematic Review and Meta‐analysis of the Literature Addressing Pain. (2nd September 2014) - Cohen, Natasha; Sommer, Doron D.; MacLean, Jonathan
Abstract : Objectives: The use of nonsteroidal anti‐inflammatory drugs (NSAIDs) post‐tonsillectomy is controversial, but recent severe complications associated with codeine and a resulting black box warning from the Food and Drug Administration have caused us to reassess their use. The aim of the study was to determine the efficacy of NSAIDs compared with other analgesics post‐tonsillectomy. Methods: We systematically searched Medline, EMBASE, the Cochrane trial registry, and Web of Science. Only randomized controlled trials (RCTs) that compared an NSAID with either placebo or non‐NSAID active comparators were included. Studies had to measure a pain‐related outcome (eg, total morphine used, pain scores). Secondary outcomes included differences in vomiting, bleeding, admission to the hospital, and return to emergency department. We did not discriminate for age of patients. RevMan 5.0 was used to synthesize and analyze the data extracted from studies reviewed. Results: Based on the meta‐analysis of the data retrieved from 60 articles, NSAIDs were found to be equivalent to other active comparators in the early postoperative period. There was also significantly less vomiting in the NSAID group. Small sample sizes of studies and heterogeneity of methods for reporting pain restricted the sample size for comparison of outcomes. Conclusions: NSAIDs are as effective as active comparators for pain relief. We recommend a large RCT to confirm these findings.